2022
DOI: 10.3390/su14031521
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Evolution: The Use of Social Networking Sites

Abstract: Online schooling has been adopted worldwide due to the COVID-19 pandemic. During quarantine, people go online for all kind of purposes, especially for amusement such as via social networking sites (SNSs). This study examined university physical education (PE) students’ SNSs usage intention using the Unified Theory of Acceptance and Use of Technology model II (UTAUT2) in Taiwan. Research respondents were selected from PE departments of 19 universities through purposive sampling method. A total of 707 questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The staggering majority of the nation, 98% in particular, are using this platform in communicating with their loved ones, particularly their relatives and friends (Statista Research Department, 2021). With all the social platforms for communication that is readily available, Facebook Messenger is one of the most commonly used in the set-up of education (Chang, Hsieh, Liao, Huang, & Lin, 2022). It has also been found that 95% of the population regardless of age, status, gender, and education are determined by the frequency of their overall, active, and interactive use of the said platform (Laor, 2022) for social media engagement (Büchi, Fosch-Villaronga, Lutz, Tamò-Larrieux, & Velidi, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The staggering majority of the nation, 98% in particular, are using this platform in communicating with their loved ones, particularly their relatives and friends (Statista Research Department, 2021). With all the social platforms for communication that is readily available, Facebook Messenger is one of the most commonly used in the set-up of education (Chang, Hsieh, Liao, Huang, & Lin, 2022). It has also been found that 95% of the population regardless of age, status, gender, and education are determined by the frequency of their overall, active, and interactive use of the said platform (Laor, 2022) for social media engagement (Büchi, Fosch-Villaronga, Lutz, Tamò-Larrieux, & Velidi, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…SNWs have given a new face to recruitment trends ( Villeda et al, 2019 ; Nikolaou, 2021 ; Rehman et al, 2021 ). Social networking websites are no longer just a place to keep in touch with social circles, but they have entered the workplaces ( Chang et al, 2022 ) in the form of social media recruiting technology (SMART) and becoming a standard mode of employee recruitment and selection.…”
Section: Introductionmentioning
confidence: 99%